Nowe szanse, nowe wyzwania i nowe zagrożenia dla edukacji związanej z rosnącą imersją uczniów w cyberprzestrzeni - Tadeusiewicz, Ryszard (Wydawnictwo Naukowe UAM, 2014)
The development and increasing number of diverse forms of all age students' immersion in cyberspace (e.g., common participation in social networking services, intensive use of electronic communication, widespread acquisition of information primarily from the Internet etc.) leads to the necessity of considering the above-mentioned factors also in any discussion about the current education. After the propagation of Internet facilities across the whole population and the emergence of numerous easily available sources of data and other information on the net – the relation between teachers and students must necessarily change in a dramatic way. Instead of the traditional role assigned previously to the teacher – that of the source of information acquired by students – now the teacher must be rather a guide in the “information jungle” sprawling over cyberspace than an information provider. The quantity and diversity of information available on the net is totally incomparable with the information that can be given to students by even the most educated and generous teacher. However, the collection of information acquired by a student from electronic sources alone is not equivalent to knowledge. There is a saying that knowledge consists of information, like a house is made of bricks. But not all heaps of bricks are houses, and not all collections of information can be considered knowledge. Both the bricks in the house walls and the information in knowledge systems must be formed by an expert. A contemporary teacher should be an expert in knowledge formation rather than an information provider. We can see here the opportunities generated by the vast amount of information available to students from the cyberspace, much bigger than the amount of information available from the teacher, or even all textbooks in the traditional teaching model. Yet we must also see the threats posed by the huge amount of imprecise, obsolete and even incorrect information which is also available on the Internet, and is often indistinguishable from the true information, the information solely valuable from the viewpoint of merit. Moreover, also examination of students is a source of threats, because the frequently employed test exams are useful for checking the information acquired by students, but are inadequate when we need to evaluate their knowledge. All the problems pointed out above are discussed in the paper, which also proposes and examines some futuristic ideas.
New Opportunities, New Challenges and New Threats to Education Resulting from Increasing Immersion of Students in Cyberspace
Keywords: education; cyberspace; e-learning; new teacher role; information versus knowledge